All the lovely bad ones ebook - Hahn, Mary Downing (2009)
Travis and his sister, Corey, can't resist a good trick—so when they learn that their grandmother's sleepy Vermont inn has a history of ghost sightings, they decide to do a little "haunting" of their own. Scaring the guests is fun, and before long, the inn is filled with tourists and ghost hunters eager for a glimpse of the supernatural. But Travis and Corey soon find out that there are real ghosts at Fox Hill. Awakened by their pranks, restless, spiteful spirits swarm the inn, while a dark and terrifying presence stalks the grounds. To lay the spirits to rest, the kids must uncover the dark history of Fox Hill and the horrors visited on its young inhabitants in the past.